RANCANG BANGUN INSTRUMEN PENGUKUR PASANG SURUT OTOMATIS PORTABEL (P2SOP) BERBASIS SISTEM ARDUINO DAN DATA LOGGER - Rohim, Gusti Akhmad; Syahdan, Muhammad; Dewi, Ira Puspita (Universitas Lambung Mangkurat, 2022)
The design of a portable automatic tide gauge instrument (P2SOP) based on the arduino system and data logger is an activity of designing and implementing an instrument that can measure sea level fluctuations during tides using an integrated mechatronics system between mechanical bodies, electronic systems in the form of input systems, processing system, output system in the form of an LCD (liquid crystal display) display and in the form of a data logger and a controlled program system. This P2SOP instrument has a mechanical body that functions as a shelter for electronic components and as a wave ripple damper so that tide level fluctuations are actually not affected by wind wave ripples. In the electronics system section, the input section uses the HC SR04 sensor, the processing system uses an integrated Arduino Uno board system and an RTC DS3231 timer system, for the output itself to be displayed in the form of an LCD (liquid crystal display) and stored in the Secure Digital Card module in the form of a data logger. It is hoped that with this P2SOP instrument in the future tide measurements can be carried out in an automated manner and minimize the occurrence of inaccurate measurement times and reading errors on manual tide measurements.